Partisans, guerillas, and irregulars : historical archaeology of asymmetric warfare - Smith, Steven D.; Geier, Clarence R. (The University of Alabama Press, 2019)
Essays that explore the growing field of conflict archaeology Within the last twenty years, the archaeology of conflict has emerged as a valuable subdiscipline within anthropology, contributing greatly to our knowledge and understanding of human conflict on a global scale. Although archaeologists have clearly demonstrated their utility in the study of large-scale battles and sites of conventional warfare, such as camps and forts, conflicts involving asymmetric, guerilla, or irregular warfare are largely missing from the historical record. Partisans, Guerillas, and Irregulars: Historical Archaeology of Asymmetric Warfare presents recent examples of how historical archaeology can contribute to a better understanding of asymmetric warfare. The volume introduces readers to this growing study and to its historic importance. Contributors illustrate how the wide range of traditional and new methods and techniques of historiography and archaeology can be applied to expose critical actions, sacrifices, and accomplishments of competing groups representing opposing philosophies and ways of life, which are otherwise lost in time. The case studies offered cover significant events in American and world history, including the French and Indian War, the American Revolution, Indian wars in the Southeast and Southwest, the Civil War, Reconstruction, Prohibition, and World War II. All such examples used here took place at a local or regional level, and several were singular events within a much larger and more complex historic movement. While retained in local memory or tradition, and despite their potential importance, they are poorly, and incompletely addressed in the historic record. Furthermore, these conflicts took place between groups of significantly different cultural and military traditions and capabilities, most taking on a "David vs. Goliath" character, further shaping the definition of asymmetric warfare.--publisher